Investigation of the pin-roller metering device and tube effect for wheat seeds and granular fertilizers based on DEM - Adilet, Sugirbay; Zhao, Kaiyuan; Liu, Guangyao; Sayakhat, Nukeshev; Jun, Chen; Hu, GuangRui; Bu, Lingxin; Chen, Yu; Jin, Hongling; Zhang, Shuo; et al. (International Journal of Agricultural and Biological Engineering, 2023)
The metering device is the central part of the seeder discharging granular fertilizers or seeds from the hopper to the colter passing through the tube. Depending on the metering device design, the batches of particles are discharged or discharged evenly. This research analyzes existing metering devices, and a new pin-roller metering device is recommended to discharge evenly high doses of granular fertilizers and wheat seeds at low rotation speeds. The objective was to adapt the metering device to precision agriculture so that a little electric motor containing gearbox drives every metering device. Therefore, the pin-roller metering device parameters were investigated to apply high doses of granular fertilizers and wheat seeds evenly. The optimal pin positions were determined according to response surface methods (RSM) by simulating the granular fertilizers and wheat seeds' behavior on DEM. The coefficient of variation (CV) and the slip rate (SR) of the particles between the pins were chosen as indicators for evaluating the pin-roller. The shape of the pin was specified, and then the number of lines, the number of pins in a line, and the pin height were chosen to optimize. The analysis of the simulation results shows the optimal parameters: the number of pins in a line is four, and the number of lines is sixteen. The SR of granular fertilizers and wheat seeds were 8% and 2%, respectively. The pin-roller metering device is compared with the six-grooved and twelve-grooved metering devices. The comparison results show that the pin-roller metering device distributes twice more uniformly than other metering devices. The CV of the granular fertilizer distribution for six-grooved, twelve-grooved, and pin-roller metering devices was 111.13%, 80.74%, and 37%, respectively. The CV of the wheat seed distribution for twelve-grooved and pin-roller metering devices was 96%, and 37%, respectively. As long as the particles interact with the tube, leaving the metering device, the effect of tube type and position is investigated. As a result, it was determined that the tube has minimal effect on the pin-roller metering device while positively impacting the six-grooved and twelve-grooved metering devices, improving the CV of the particle distribution into the soil. Keywords: pin-roller, metering device, DEM, coefficient of variation, slippage rate, tube DOI: 10.25165/j.ijabe.20231602.7721 Citation: Adilet S, Zhao K Y, Liu G Y, Sayakhat N, Chen J, Hu G R, et al. Investigation of the pin-roller metering device and tube effect for wheat seeds and granular fertilizers based on DEM. Int J Agric & Biol Eng, 2023; 16(2): 103－114.